Hill-farming in Himalayas Another enemy in fray - Thakur, Yashasvi; Sharma, Vikas Kumar (Indian Farming, 2024)
The Himalayan region of Himachal Pradesh, recently devastated by flash floods, now faces another threat–the invasion of the Fall Armyworm (FAW). Originating from the Americas, FAW has rapidly spread across continents, reaching Africa, Asia, Australia, and even New Zealand. In India, its presence was first detected in 2018, with subsequent reports from all states except Himachal Pradesh and Jammu and Kashmir. However, in 2020, FAW infested maize crops in Himachal Pradesh's Una district, posing a significant threat to the region's agriculture-dependent livelihoods and food security. This article highlights the challenges posed by FAW in Himachal Pradesh, emphasizing the urgent need for effective management strategies to mitigate crop losses and safeguard agricultural sustainability in the face of this invasive pest.